Tree islands: the bellwether of Everglades ecosystem function and restoration success. (5th September 2016) - Wetzel, Paul R.; Sah, Jay P.; Ross, Michael S.
Abstract: Everglades tree islands are patches of woody vegetation ranging in size from 0.1 to 70 ha embedded in a marsh matrix. Tree islands are an essential component of the tree island–ridge–slough topographic continuum and the trees provide a mechanism for the accumulation of phosphorus in the landscape, enhancing landscape biocomplexity. This article reviews the literature of tree island ecology and describes the predicted effects of five ecosystem restoration scenarios on tree islands. Elevations of the highest points on 404 islands across the Everglades were used to assess the effects of the scenarios at a landscape level, while the plant communities of nine islands were modeled to assess local effects. Evaluation of the restoration scenarios were based on three critical components needed to maintain and restore tree islands: hydrology that allows the survival of woody species, seasonally appropriate water flow to move nutrients off the heads of islands, and oligotrophy. All restoration options generally improved water conditions for tree growth, although flooding of islands in some areas was predicted to increase. Scenarios with the greatest amount of decompartmentalization and largest capacity to remove phosphorus from water entering the Everglades provided the best chance of delivering vigorous pulses of sheet flow in directions parallel to historic flows and maintaining oligotrophy. Tree islands are "bellwethers" of restoration actions because their maintenance on the landscape requires multiple ecosystem functions.